Implementasi Metode SMART dan MAUT dalam Menentukan Ekstrakulikuler Siswa SMA Plus Nurul Mubin NW - Hadi, Wahyu; Saikin, Saikin; Fahmi, Hairul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Selecting appropriate extracurricular activities that align with students’ interests and talents is an important factor in developing their potential and improving non-academic achievements. However, the manual and subjective selection process often leads to inaccuracies in determining suitable activities for students. This study aims to implement the Simple Multi Attribute Rating Technique (SMART) and Multi Attribute Utility Theory (MAUT) methods in a decision support system for extracurricular selection at SMA Plus Nurul Mubin NW, to ensure decisions are made more objectively and measurably. The research was conducted through several stages, including problem identification, data collection through observation, interviews, and questionnaires distributed to students and teachers. The criteria used include interest, talent, free time, and parental support. The results of the calculations using both methods show consistent outcomes, where Student 1 (S1) obtained the highest score of 0.73, making it the best alternative. The similarity of results between the SMART and MAUT methods indicates a high level of reliability and validity in supporting multi-criteria decision-making. Therefore, the application of these two methods is considered effective in helping schools determine the most suitable extracurricular activities for students, contributing to improving the quality of extracurricular management in educational environments.